Computed tomographies and cancer risk in children: a literature overview of CT practices, risk estimations and an epidemiologic cohort study proposal - Krille, Lucian; Weisser, Gerald (Radiation and environmental biophysics, 2012)
Radiation protection is a topic of great public concern and of many scientific investigations, because ionizing radiation is an established risk factor for leukaemia and many solid tumours. Exposure of the public to ionizing radiation includes exposure to background radiation, as well as medical and occupational exposures. A large fraction of the exposure from diagnostic procedures comes from medical imaging. Computed tomography (CT) is the major single contributor of diagnostic radiation exposure. An increase in the use of CTs has been reported over the last decades in many countries. Children have smaller bodies and lower shielding capacities, factors that affect the individual organ doses due to medical imaging. Several risk models have been applied to estimate the cancer burden caused by ionizing radiation from CT. All models predict higher risks for cancer among children exposed to CT as compared to adults. However, the cancer risk associated with CT has not been assessed directly in epidemiological studies. Here, plans are described to conduct an historical cohort study to investigate the cancer incidence in paediatric patients exposed to CT before the age of 15 in Germany. Patients will be recruited from radiology departments of several hospitals. Their individual exposure will be recorded, and time-dependent cumulative organ doses will be calculated. Follow-up for cancer incidence via the German Childhood Cancer Registry will allow computation of standardized incidence ratios using population-based incidence rates for childhood cancer. Dose-response modelling and analyses for subgroups of children based on the indication for and the result of the CT will be performed.